Group Cohesiveness and Performance: The Moderating Effect of Diversity - Soldan, Zhanna (Common Ground Publishing, 2010)
The purpose of the present study was to examine the relationship between cohesiveness and performance and the role diversity (full-time work experience) plays in this relationship. A total of 154 student groups participated in the study. The results predicted and confirmed that a positive relationship between group cohesiveness and performance exists. Furthermore, the interaction of diversity with group cohesiveness was positively related to performance. Specifically, observed variations in performance appear to be predictive of cohesiveness only when the group is highly diverse in terms of full-time work experience. When group diversity is low, cohesiveness appears to be more or less unrelated to performance. Practical and research implications will be discussed and directions for future research suggested.